SISTEM INFORMASI DONOR DARAH BERBASIS ANDROID PADA UNIT TRANSFUSI DARAH PALANG MERAH INDONESIA (UTD PMI) KOTA PEKANBARU - Anita Febriani; Rika Melyanti; Rizky Wahyu Syahputra (STMIK Hang Tuah Pekanbaru, 2020)
Blood is one of the most important parts in the human body because blood has a function to circulate the juice, carry oxygen, circulate hormones, and others. If humans reduce blood caused by accidents or anemia, so that humans lack blood or store dirty blood in the body, then it can cause diseases that endanger the health of even someone. Blood donor activity is an activity of the process of blood transfer from donors to people who lack blood. The process is carried out by those who carry out blood processing processes such as the Blood Transfusion Unit (UTD) under the auspices of the Indonesian Red Cross (PMI). UTD PMI Pekanbaru City only has a web-based blood donor information system, so UTD PMI Pekanbaru City wants to keep up with the times where many users use smartphones so they want to upgrade from the web version to the Android version. The reason for the improvement of this system aims to reduce hosting costs to be paid when using a web system and Android-based information system does not require typing too much when the user will carry out an order to the system, its use is not limited by space and place, and does not really need a connection that is prime to run the system. Android-Based Donor Information System in the Indonesian Red Cross Blood Transfusion Unit (UTD PMI) Pekanbaru City can help all people to find out about information about blood donations well by using Android-based smartphones as interesting media.